Long‐term follow‐up comparison of two different bi‐layer dermal substitutes in tissue regeneration: Clinical outcomes and histological findings. Issue 5 (28th March 2018) - De Angelis, Barbara; Orlandi, Fabrizio; Fernandes Lopes Morais D'Autilio, Margarida; Scioli, Maria G; Orlandi, Augusto; Cervelli, Valerio; Gentile, Pietro
Abstract : Double layer dermal substitute (DS) consist of a 3‐dimensional collagen structures and a superficial silicon layer that are positioned within the defect provide to promote tissue regeneration in skin wounds. DS often have unique physical characteristics due to differences in manufacturing techniques. The aim of this study is the clinical and histological comparison of Nevelia and Integra double layer DSs in patients with post‐traumatic injury wounds. Thirty patients with post‐traumatic wounds localised on the inferior limbs were randomised in 2 groups Nevelia or Integra, followed by autologous dermal epidermal graft (DEG). Clinical results were evaluated through the healing time; Manchester Scar Scale (MSS) and Visual Analog Scale (VAS) at 1, 2, and 3 weeks and after 1 and 3 years. Histological and immunohistochemical evaluation were performed at 0, 2, and 3 weeks. The difference in healing time between groups ( P = .467, log‐rank test), pain and self‐estimation was not statistically significant after 35, 42, and 49 days and at 1‐year follow up. Histological data showed evident healing of wound after 2 weeks compared with preoperative with both DSs. At 3 weeks reepithelialisation and dermal regeneration were evident with both substitutes; however Nevelia showed early regenerative properties in terms of epidermal proliferation and dermal renewal compared with Integra. Nevelia showed also a more evident angiogenesis vs Integra evaluated as α‐SMA immunohistochemistry. Differences in the MSS score were statistically significant at 3 years follow up in favour of Nevelia group ( P = .001). At long‐term follow up, Nevelia showed a better clinical outcome measured as MSS score vs Integra measured as MSS. Histological and immunohistochemistry data showed that Nevelia allows faster neoangiogenesis and tissue regeneration with neoformed tissue architecture closer to the physiology of the skin.